Measurement of The Centric Relation-Maximum Intercuspation Difference: MRI Versus The SAM® Mandibular Position Indicator - Berna Turası; Sibel Biren; Arzu Arı-Demirkaya (Galenos Yayinevi, 2006)
The aim of this study was to generate normative data about condylar positions and condyle-disc relationship in healthy individuals, and to compare condylar po -sitions on Magnetic Resonance Images (MRI) to articulator generated condylar positions measured with the SAM® Mandibular Position Indicator (MP!) regarding the difference between condylar positions in centric relation (CR) and maximum intercuspation (MI). The study group consisted of 30 subjects with normal occlusion and clinically healthy temporomandibular joints. Centric occlusion-maximum intercuspation differences were recorded using the SAM® MPI. Subsequent MR images were taken with the mandible in CR and MI, and the difference in condylar position compared to the MPI findings of the same subjects. MRI and MPI data of the same individuals did not coincide (antero-posterior: p=0.000; vertical: p=0.007), and condyles were concentric in 73% and 87% for right and left sides respectively.